Next-Generation Immunotherapies to Improve Anticancer Immunity - Shi, Yaoyao; Tomczak, Katarzyna; Li, June; Ochieng, Joshua K.; Lee, Younghee; Haymaker, Cara (Frontiers in Pharmacology, 2021)
Checkpoint inhibitors are current prevalent immunotherapies for advanced cancer treatment. Concerns exist regarding their relatively low response rate, limited beneficial cancer types, and their unignorable side effects. Checkpoint inhibitors aim at reinvigorating exhausted or suppressed T cells in the tumor microenvironment (TME). However, the TME contains various other immune cell subsets interacting and determining the fate of cytotoxic T cells together. The activation of cytotoxic T cells is initiated by antigen cross presentation of dendritic cells (DCs). DC could also release chemokines and cytokines to recruit and foster T cells. B cells can also present antigens to T cells and produce tumor-specific antibodies. Neutrophils, one myeloid cell subset in TME, impede the proliferation and activation of T cells. The TME also consist of cytotoxic innate natural killer (NK) cells killing tumor cells efficiently. NK cells can eradicate MHC I-negative tumor cells which escape cytotoxic T cell- mediated destruction. A thorough understanding of their immune mechanism will lead to further development of potential therapeutic strategies. We also evaluate the current clinical outcome of drugs targeting these immune cells for further improvement and possible combined immunotherapy strategies.